HUBUNGAN ANTARA KAIDAH AGAMA DENGAN KAIDAH-KAIDAH LAINNYA - , Cecep Cahya Supena (Program Studi Ilmu Pemerintahan FISIP Universitas Galuh, 2024)
Every human being in living his life always has various kinds of needs and interests. In order to fulfill their needs and interests in life, sometimes humans collaborate with each other, but sometimes they also clash with each other. To avoid clashes that could be dangerous, human life needs to be regulated and controlled to create security, order and justice. The regulation and control referred to is carried out through the application of rules. The existence of rules for human life is absolutely necessary, because they can be used as instructions or guidelines for humans in living their personal, social, national and state lives. Not only citizens must comply with these rules, but the state (government) must also comply with these rules in exercising its power, so that there will be no arbitrariness (absolute or authoritarian) in exercising its power.